2006
DOI: 10.1080/00926230600834695
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Variables of Sexual Satisfaction in Chile

Abstract: This study analyzed psychosocial variables of sexual satisfaction in Chile using data from the COSECON survey. Participants were 5,407 subjects (2,244 min and 3,163 women, aged 18-69 years). We used a cross-sectional questionnaire with a national probability sample. Data were collected using a thorough sexual behavior questionnaire consisting of 190 face-to-face questions and 24 self-reported questions. A single item included in the COSECON questionnaire assessed sexual satisfaction. Results showed that high e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
1
28

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 14 publications
3
58
1
28
Order By: Relevance
“…In the study of Barrientos that aimed to investigate the relationship between psychosocial variables and sexual satisfaction, education was one of the predictors of sexual satisfaction among women (6). This was in contrast to the results of the study by Rahmani et al (12) who found no relationship between education and sexual satisfaction which is similar to the results of this study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In the study of Barrientos that aimed to investigate the relationship between psychosocial variables and sexual satisfaction, education was one of the predictors of sexual satisfaction among women (6). This was in contrast to the results of the study by Rahmani et al (12) who found no relationship between education and sexual satisfaction which is similar to the results of this study.…”
Section: Discussioncontrasting
confidence: 57%
“…Hence, identification of factors affecting sexual satisfaction in addition to strengthening the interpersonal relationship, play important roles in the stability of the family system (5). These factors include socio-demographic characteristics, socio-religious beliefs, socio-economic status (6), social support and family relationships (7), diseases, depression, psychic stress, drug usage, infertility, pregnancy, delivery (8) and use of contraceptive methods (9).…”
Section: Introductionmentioning
confidence: 99%
“…Barrientos et al found that high levels of education are associated with better sexual performance. 24 Regardless of contraceptive method; education for over 12 years has been associated with a reduced risk of sexual dysfunction up to 36% in the general population, because the scientific attitude and awareness of sexual issues increase with level of education. 25 According to the study, there was a significant inverse relationship between the number of children and female sexual function index so that women with more children had lower sexual function index.…”
Section: Discussionmentioning
confidence: 99%
“…An effective relationship can promote sexual stimulation and is needed for beginning or refusing sex (Spercher & McKinney, 1993). Researches also have shown the relationship between sexual satisfactions with satisfaction from spouses' relationship (Barrientos, 2006). Dissatisfaction from sexual relationship will lead to deep conflicts in spouses' relationships (D. Olson, S. Olson, & Larson, 2008, translated by Darini & Navabinejad, 2012 and conflicts between spouses (Moovahed & Azizi, 2013).…”
mentioning
confidence: 99%
“…Runcan, Constantineanu, Iclics, and Popa (2012) also have shown in their studies that parents who gained high score in variables of father-child interaction, have more communication skills such as preferring to talk with their children without advising, not saying the things which are bothering, listening to what a child says carefully and encourage the child to talk and express emotions. Sexual satisfaction is considered as the other important indicators of successful marriage and family health and considering the rate of couples' sexual satisfaction, the rate of spouse's interactions can be identified (Barrientos, 2006). Sexual satisfaction refers to the rate of each person's pleasure or joy from sexual relationship (Harvey, Weuzel, & Sprecher, 2005).…”
mentioning
confidence: 99%